2016
DOI: 10.1007/s10067-016-3378-7
|View full text |Cite
|
Sign up to set email alerts
|

A survey of anatomical items relevant to the practice of rheumatology: upper extremity, head, neck, spine, and general concepts

Abstract: Objective. To identify those anatomical items of the upper extremity and spine that are potentially relevant to the practice of rheumatology. shoulder items, and 23 (17. 6%) head, neck and spine items. Methods Conclusions.As a result of this Delphi exercise, a group of practicing academic rheumatologists with an interest in clinical anatomy compiled a list of anatomical items that were deemed important to the practice of rheumatology.We suggest these items be considered curricular priorities when training rheu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…One is the flat dorsal distal head of the radius, and the other is the dorsal tubercle of the radius, located distally on the flat surface of the radius adjacent to the radiocarpal joint. Identifying the dorsal tubercle of the radius was emphasized in a Delphi study of anatomical structures useful to rheumatologists [ 17 ]. Pantukosit’s fascinating report [ 8 ] observed that all but one of 30 FIS cases occurred on the dominant side, and most of the patients were rice farmers who performed repetitive, forceful wrist movements.…”
Section: Discussionmentioning
confidence: 99%
“…One is the flat dorsal distal head of the radius, and the other is the dorsal tubercle of the radius, located distally on the flat surface of the radius adjacent to the radiocarpal joint. Identifying the dorsal tubercle of the radius was emphasized in a Delphi study of anatomical structures useful to rheumatologists [ 17 ]. Pantukosit’s fascinating report [ 8 ] observed that all but one of 30 FIS cases occurred on the dominant side, and most of the patients were rice farmers who performed repetitive, forceful wrist movements.…”
Section: Discussionmentioning
confidence: 99%
“…The strengths and limitations of our survey methodology were discussed in our previous paper that dealt with the upper extremity and spine [3]. Briefly, one strength includes the individual contribution and then the merging of items by all members of our group.…”
Section: Discussionmentioning
confidence: 99%
“…The combined list contained 470 items: 137 (29.15%) pelvis and hip items, 82 (17.45%) knee items, 168 (35.74%) ankle and foot items, 68 (14.46%) neurologic items, and 15 gait items (3.20%). This master list was sent to the same GMAC and international experts that participated in the initial study [3], via a oneround, web-supported Delphi survey (SurveyMonkey Inc., Palo Alto, CA, USA). The international experts were from Boston (RAK) and New Orleans (JB), USA; La Coruña (FJTS), Spain; Leeds (DMcG), UK; and Toronto (SC), Canada.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation